Sukuk Bond in Pakistan: an analysis of islamic mode of financing for investors - Raees, Sakheela; Raheem, Zakir; Zakir, Anam (Archives of Business Research, 2017)
Banking and financial system in an economy acts as blood circulation in body. Just as effective and efficient blood circulation ensures healthy and sound body similarly strong banking and financial system ensures economic efficiency and development. The basic objective of financial system is to find comprehensive solutions to existing practical problems. Islamic banking and financial industry is rapidly growing all over the world predominantly in Islamic countries. Islamic finance industry has arisen as best alternative to conventional financial system by providing better products and effective means of financing. The products introduced by Islamic finance industry are recognized all around the globe. Islamic banking and finance industry is making positive contribution to all segments of society like trade and industry. Islamic finance industry offer different products to investors for financing purposes. The study relates to Islamic Banking specifically focusing on Islamic bonds. Islamic bonds have been developed as capital market instrument in past few decades. The purpose of this study is to identify those factors that can increase the investment in sukuk. Present study is quantitative research in which mix method design is adopted to conduct the analysis. This study contains three questions. First question identifies the difference between conventional bonds and sukuk. Second question describes the structure of the sukuk. These questions were answered from the literature available on this field. Third question identifies those factors which enhance the investment in sukuk in Pakistan. To investigate this, a structured and self-administered questionnaire was constructed to collect the response of current and potential investors. The respondents were teachers who are teaching in University of the Punjab. The data was collected by distributing 285 questionnaires among respondents. The questionnaire consisted of two sections based on five point likert scale. The questionnaire was examined for validity and reliability. To check and determine the predictive relationship among dependent variable and independent variables linear regression model is used in this study. The questionnaire contains five independent variables; Knowledge about the Sukuk, Islamic spirit, and Return on investment, Mechanism, and Trust on issuing authority and one dependent variable, as investment in Sukuk. The empirical results of study indicates that Knowledge about the Sukuk has positive, significant and the strongest relationship with investment in Sukuk, and Islamic spirit has positive, significant and stronger relationship with investment in Sukuk. Return on investment has positive, significant and strong relationship with investment in Sukuk whereas the relationship with Mechanism and investment is positive and significant but is weaker as compared to these three variables. Moreover relationship of Trust on issuing authority is although positive but insignificant and has the weakest relationship.